Upaya Meningkatkan Kerja Sama Peserta Didik Melalui Strategi Think Pair Share Pada Mata Pelajaran Akidah Akhlak Di Kelas VII MTs Al-Ittihadiyah Jalan Bromo - Arlina Arlina; Dea Yolanda Damanik; Fahriza Hasri Siregar; Nadya Arifah Malasari Harahap; Nur Hidayah (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
This study aims to determine the learning process using the method think pair share on the subjects of moral creed in class VII MTs Al-Ittihadiyah Jalan Bromo and to see the use of this method will increase learning interest and results Learning that affects students' self-change and sense of work responsibility the same between students. The research method used is Classroom Action Research (PTK) or Classroom Action Research where this research has a very important role and strategies to improve the quality of learning if implemented properly and right. The results of the study explained that Akidah Akhlak learning in class VII MTS Al-Ittihadiyah is dominated by teachers using less learning methods Vary. Teachers often use the lecture method. The process of learning moral creed In this study carried out with the stages of class action research, namely planning, action/execution, observation, and reflection. Increased participant learning cooperation Students can be seen from the student cooperation questionnaire conducted in 1 cycle only By using pretest and postest questionnaires at one meeting.